Action Understanding Promoted by Interoception in Children: A Developmental Model - Zhou, Hui; Gao, Qiyang; Chen, Wei; Wei, Qiaobo (Frontiers in Psychology, 2022)
Action understanding of children develops from simple associative learning to mentalizing. With the rise of embodied cognition, the role of interoception in action observation and action understanding has received more attention. From a developmental perspective, this study proposes a novel developmental model that explores how interoception promotes action understanding of children across ages. In early infancy, most actions observed in infants come from interactions with their caregivers. Babies learn about action effects through automatic interoceptive processing and interoceptive feedback. Interoception in early infancy is not fully developed, such as the not fully developed gastrointestinal tract and intestinal nervous system. Therefore, in early infancy, action understanding is based on low-level and original interoceptive information. At this stage, after observing the actions of others, infants can create mental representations or even imitate actions without external visual feedback, which requires interoception to provide internal reference information. By early childhood, children begin to infer action intentions of other people by integrating various types of information to reach the mentalizing level. Interoception processing requires the integration of multiple internal signals, which promotes the information integration ability of children. Interoception also provides inner information for reasoning about action intention. This review also discussed the neural mechanisms of interoception and possible ways by which it could promote action understanding of children. In early infancy, the central autonomic neural network (CAN) automatically processes and responds to the actions of caregivers on infants, providing interoceptive information for action understanding of infants. In infancy, the growth of the somatomotor system provides important internal reference information for observing and imitating the actions of infants. In early childhood, the development of interoception of children facilitates the integration of internal and external information, which promotes the mentalization of action understanding of children. According to the proposed developmental model of action understanding of children promoted by interoception, there are multilevel and stage-dependent characteristics that impact the role of interoception in action understanding of children.